Glycoproteins of Sindbis Virus: Preliminary Characterization of the Oligosaccharides - Sefton, Bartholomew M. (1974)
The carbohydrate content of Sindbis virus was determined by gas chromatographic analysis. The two viral glycoproteins were found to be approximately 8% carbohydrate by weight. Mannose is the sugar present in the largest amount. Smaller amounts of glucosamine, galactose, sialic acid, and fucose were also detected. Each of the two viral glycoproteins appears to contain two structurally unrelated oligosaccharides. Two of the three Sindbis-specific glycoproteins found in infected chick cells were shown to contain short, unfinished oligosaccharides.